2009
DOI: 10.1177/0885328209355332
|View full text |Cite
|
Sign up to set email alerts
|

Design and Dynamic Culture of 3D-Scaffolds for Cartilage Tissue Engineering

Abstract: Engineered scaffolds for tissue-engineering should be designed to match the stiffness and strength of healthy tissues while maintaining an interconnected pore network and a reasonable porosity. In this work, we have used 3D-plotting technique to produce poly-L-Lactide macroporous scaffolds with two different pore sizes. The ability of these macroporous scaffolds to support chondrocyte attachment and viability were compared under static and dynamic loading in vitro. Moreover, the 3D-plotting technique was combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 37 publications
1
48
0
Order By: Relevance
“…Additive manufacturing (AM) technologies have shown promise in developing scaffolds with rigorously controlled internal architectures and mechanical properties for tissue and organ regeneration [172][173][174]. However, viscosity constraint is a stumbling block for the majority of extrusion-based AM techniques [175,176].…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…Additive manufacturing (AM) technologies have shown promise in developing scaffolds with rigorously controlled internal architectures and mechanical properties for tissue and organ regeneration [172][173][174]. However, viscosity constraint is a stumbling block for the majority of extrusion-based AM techniques [175,176].…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…The presence of both macro and micropores are important in 3D scaffolds, as macropores (>50 µm) promote cell migration [68] and micropores promote cell–cell interaction and mass transport, which improve tissue formation especially in vivo [69]. Titanium alloy constructs with a small average pore size (13 μm) form thicker cartilage tissue with significantly greater proteoglycan and cell density than those with larger pore sizes (43 and 68 μm) [67].…”
Section: Scaffold Design For Cartilage Tissue Engineeringmentioning
confidence: 99%
“…An appropriate physicochemical environment that accounts for a physiological intracellular stress state deriving from the cell-biomaterial interaction may favor the recovery of a phenotypic cell expression (1,2). The maintenance of such a physiological adhesive configuration, which is primarily related to the microarchitecture of the scaffold, (8,12,13,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). However, some results have indicated that chondrocyte phenotype and biosynthetic activity improved in collagen matrices containing smaller pores (28,29).…”
Section: Introductionmentioning
confidence: 99%